DANCES OF A TIME: PEDAGOGIES OF ABSENCE IN THE MIDDLE OF THE PANDEMIC - Carolina Romano de Andrade; Renata Fernandes dos Santos; Luiza Romani Ferreira Banov (Cena, 2021)
This paper proposes to reflect about dance, in its educational context, from the situation caused by the Covid-19 pandemic. The question that guides the text comes from the problem of teaching an art of the presence in a remote way: what was it possible to gather from this experience in order to project changes in dance teaching? Thus, the introduction presents the context of remote emergency teaching with reference to dance practice. Following this, three aspects related to dance learning are described: a time for listening, a poetics of distance and a state of being in the present. In the last part, the article draws conclusions on dance and its contributions to this process of artistic pedagogical reformulation, which demanded reinvention from all involved: children, educators and families.